Researching the development gap between the hinterland and the coast—evidence from the island of Crete - Andriotis, Konstantinos (My University, 2006)
Past research has demonstrated that island tourism is mainly developed along the coast, and that hinterland areas face inherent disadvantages in developing their tourism industry. Peripherality; rurality; limited infrastructure and facilities; and the increasing demand of international tourists for beach holidays have shown that the alternatives of hinterland areas for 'touristisation' and self-sustaining growth are limited. In effect, rural population tends to leave their birthplaces and migrate to the cities and the coastal resorts in the search for better life and employment opportunities. All the above issues reported in tourism literature are evident in Crete. Through a literature review and a statistical analysis it was found that in Crete there is an unequal distribution of tourist spending and accentuated regional imbalances with the vast majority of tourism activity concentrated on the coast and economic activity in the hinterland mainly directed to agriculture. Bearing all these in mind, it is the aim of this paper to study the development gap between the hinterland and the coast and provide recommendations for bridging this gap.
Keywords: Coast; Crete; Development gap; Hinterland; Rurality; Tourism